His jet-set nights with the innocent - Roscoe, Pippa (Harlequin presents, 2023)
Billionaire Mateo Marin wants nothing to do with archaeologist Evelyn Edwards, his late father's stunning assistant. Not when their work always came before his family's happiness. So when Evie gate-crashes his birthday party, he's outraged--if inexplicably drawn to her. Evie's professional reputation means everything to her, and she needs Mateo's help to save it. But embarking on a quest together around the world is more than innocent Evie bargained on. From Spain to Shanghai, each city holds a different adventure. Yet one thing is constant: their intoxicating attraction!